Tren Inovasi Digital Pasca Pandemi Covid-19 Pada Keberlanjutan Wirausaha Start-Up Di Indonesia - Hanifah Azzahra1 (Journal Science Innovation and Technology (SINTECH), 2021)
Entrepreneurship (Entrepreneurship) is a person's process of identifying and developing a vision that will be brought to life, an entrepreneur must have the ability to innovate and be creative. The emergence of motivation to be entrepreneurial in someone when that person has a strong intention to have income. Given the importance of entrepreneurship, especially during the Covid-19 era like this, digital technology is an opportunity to start new businesses and create competences in the digital entrepreneurial ecosystem. Digital technology is not only for starting a new business, but a tool for running an existing business, with the help of this digital technology entrepreneurship will make it easier to promote products. Digital technology as an opportunity to get better performance results.